2019
DOI: 10.4236/as.2019.108082
|View full text |Cite
|
Sign up to set email alerts
|

Status of Root-Knot Nematode (<i>Meloidogyne</i> Species) and Fusarium Wilt (<i>Fusarium oxysporum</i>) Disease Complex on Tomato (<i>Solanum lycopersicum</i> L.) in the Central Rift Valley, Ethiopia

Abstract: Development of diseases in cultivated crops depends on the complex interrelationship among host, pathogen and prevailing environmental conditions. In nature, plants are rarely, if ever, subject to the influence of only one potential pathogen and this is especially true of soil-borne pathogens like fusarium wilt (Fusarium oxysporum). In the present study, the co-occurrence of root-knot nematode (Meloidogyne species) and Fusarium oxysporum f.sp. lycopersici was surveyed in the main tomato growing areas of the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…had colonies that were white or accompanied by purple or pink coloration at the center of the colony. This was consistent with findings from Kassie (2019) that reported F. oxysporum on PDA media forms a mycelium which is insulated and initially white and gradually turns to purple. The occurrence of color differences over time is more likely due to the accumulation of colors produced during the growth of F. oxysporum (Ambar et al, 2019).…”
Section: Identification Of Pathogenic Fungisupporting
confidence: 93%
See 3 more Smart Citations
“…had colonies that were white or accompanied by purple or pink coloration at the center of the colony. This was consistent with findings from Kassie (2019) that reported F. oxysporum on PDA media forms a mycelium which is insulated and initially white and gradually turns to purple. The occurrence of color differences over time is more likely due to the accumulation of colors produced during the growth of F. oxysporum (Ambar et al, 2019).…”
Section: Identification Of Pathogenic Fungisupporting
confidence: 93%
“…The synergistic interaction between D. dipsaci and Rhizoctonia solani were also reported in sugar beets (Hillnhütter et al, 2011). Other association between M. incognita and F. oxysporum in tomato plants caused complex diseases (Kassie, 2019). Therefore, investigation on the causal agents of bulbs rot disease was done and the role of both nematode and fungi were determined and the possible interaction between both of them in bulb rot disease incidences.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Previously, it has been reported that Meloidogyne spp. causes severe infection in tomato when followed by Fusarium oxysporum infestation [16][17][18]. It induces changes in developmental and morphological attributes of crops, in addition to systemic symptoms such as wilting, dwarfing, yellowing, and susceptibility to other pathogens [19].…”
Section: Introductionmentioning
confidence: 99%